A Game-Based Approach to Raise Quality Awareness in Ramp-Up Processes. Issue 1 (1st January 2016) - Brauner, Philipp; Philipsen, Ralf; Fels, Antonia; Fuhrmann, Marco; Ngo, Quoc Hao; Stiller, Sebastian; Schmitt, Robert; Ziefle, Martina
Abstract : Today's production systems are complex sociotechnical systems. Both technical challenges, as well as the integration of human employees with their diverse abilities, wants, and needs, must be considered. Due to a growing number of product variants, shorter lead times, and global supply chains, planning production systems is becoming increasingly difficult, both on the technical and human levels. The highly volatile and uncertain character of production systems is intensified by the growing complexity and need for results in shorter decision times for ramp-up management. To handle the increasing complexity, human decision makers must be adequately trained for the ramp-up period. Therefore, the influential factors and their magnitude from both the technical and the human perspective must be identified and understood. This knowledge can help to manage the complexity of ramp-up processes, reduce the disturbances within the processes, and strengthen their overall resilience against failures. To adequately understand the human and technical factors that relate to ramp-up processes, it's necessary to have an experimental framework. This framework should support the identification and quantification of sociotechnical factors, enabling practitioners and researchers to model suitable interventions. In this article, the authors propose, develop, and evaluate a business simulation game that serves as such an empirical framework. The game is furthermore suitable to train managers before the ramp-up process. The achieved performance in the business simulation game may be used to evaluate a person's suitability for the task and to identify individual training potential.